Optimization of sodium extraction from soil by using a central composite design (CCD) and determination of soil sodium content by ion selective electrodes - Sevinç Karadağ; Emel Eren; Ebru Çetinkaya; Selin Özen; Seda Deveci (Eurasian Journal of Soil Science, 2016)
Rapid determination of sodium (Na) ions in soil samples using ion selective electrodes (ISE) was investigated in this study. The compatibility of ISEs with soil extraction solution is a challenging subject as various effects such as pH, ionic strength and other interferences have to be considered as well as efficiency of the extraction solution. Because almost every type of sodium salt is soluble in water, and the pH of water is suitable for ISE studies, it was chosen as the soil extractant. Firstly, the extraction parameters were optimized by using a central composite design (CCD), secondly thirty agricultural soil samples were extracted with water and the extracts were measured by Na-ISE in a previously developed flow system. The results were compared with ion chromatography (IC) as the reference method, and the regression analysis between IC and ISE results yielded a high correlation (R² = 0.9408). It was concluded that, ion selective electrodes can be used with water as an extraction solution for rapid determination of sodium in soil samples.